LEGAL CERTAINTY AS A FOUNDATIONAL PRINCIPLE OF PROFESSIONAL ACCOUNTABILITY FOR MEDICAL LABORATORY TECHNOLOGISTS IN CASES OF ETHICAL CODE VIOLATIONS - Dahlan Sitohang; Ariy Khaerudin; Aziz Zaelani (Awang Long Law Review, 2026)
The development of healthcare services necessitates enhanced professionalism and legal accountability among health professionals, including Medical Laboratory Technologists (MLTs), who play a strategic role in supporting diagnostic accuracy and ensuring patient safety. Violations of the professional code of ethics by MLTs may give rise to legal consequences that affect patients, healthcare institutions, and public trust. This study aims to analyze the legal framework governing the responsibilities of Medical Laboratory Technologists, the forms and mechanisms of legal accountability arising from violations of the professional code of ethics, and the mechanisms for resolving such violations in order to achieve legal certainty. This research employs a normative legal research method with statutory and case-based approaches. The data were obtained through a literature review of primary, secondary, and tertiary legal materials, which were analyzed qualitatively using deductive reasoning. The findings indicate that the responsibilities of Medical Laboratory Technologists have been comprehensively regulated under statutory provisions and professional codes of ethics, emphasizing compliance with professional standards, standard operating procedures, and patient safety principles. The legal accountability of MLTs is multidimensional, encompassing administrative, civil, and criminal aspects, applied proportionally based on the nature of the violation and its resulting consequences. The mechanism for resolving violations of the professional code of ethics is conducted in a tiered manner through professional organizations and disciplinary boards, as well as through litigation and non-litigation processes, thereby ensuring legal certainty and balanced protection for both patients and healthcare professionals.